Influência da incorporação de nanofibras de poliamida 6 com e sem nanotubos de carbono como reforço de prótese parcial fixa adesiva - Girotto, Bruna Costa [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The aim of this study was to evaluate the behavior of reinforced composites with polyamide 6 fibers aligned (6000 rpm) and alignment (120 rpm) with or without CNT using the flexural strength test. After preparation of nanofibers aligned nylon 6 (6000 rpm) and alignment (120 rpm) with and without incorporation of nanotube carbon by the method of electrospinning, were performed one control group (n = 10) and 4 experimental groups (n = 40) G1: Control (just resin Charisma - Heraeus Kulzer) ;G2 Resin + N6 aligned (6000 rpm) + CNT; G3:Resin + N6 alignment (120 rpm) + CNT; G4: Resin + aligned ( 6000 rpm) N6. G5: Resin + N6 alignment (120 rpm). The fibers were cut to the dimensions of 0,3 x 15 mm and were applied an adhesive at the surface (Single Bond 2) for 5 min and cured. In the matrix, was added resin in the proximal box (Charisma A2, Heraeus Kulzer) and cured for 40 s. (power 1100 mW / cm²). A first layer of resin and on the resin was deposited. The resin layers specimens were light irradiated with three overlapping exposures delivered. For each resin layer were light irradiated for 40 sec. The samples were tested with a cross-speed of 1 mm / min, and a 50 Kgf at Universal testing machine (EMIC mod.DL2000). The Dunnet test showed that only the nanotube group was significantly different from the control group. The ANOVA two-way indicates that the nanotube factor was statistically significant (p < 0.05) and there is no interaction between factors and orientation nanotube. The presence of nanotube showed lower fracture resistance values for aligned and unaligned groups. The results of this study showed that the orientation of the fibers does not influence the strength of composite resins and the incorporation of nylon nanofibers with carbon nanotubes decreased the fracture resistance values. The presence of the fibers has not been able to improve the strength of the material in any of the...

Este trabalho se propõe avaliar o comportamento de resinas compostas reforçadas com nanofibras de poliamida 6 (nylon/N6) alinhadas (6000 rpm) e desalinhadas (120 rpm), com e sem nanotubos de carbono (CNT), através do teste de resistência à flexão. As nanofibras foram obtidas pela técnica de eletrofiação. Nela foram produzidas nanofibras de nylon 6 alinhadas (6000 rpm) e desalinhadas (120 rpm) com e sem incorporação de nanotubos de carbono (CNT) para serem utilizadas no trabalho. A metodologia utilizada é constituída de 5 grupos experimentais: Grupo 1: controle sem fibras (n=10), Grupo 2: Resina Charisma + N6 alinhado (6000 rpm) + CNT; Grupo 3: Resina Charisma + N6 desalinhado (120 rpm) + CNT; Grupo 4: Resina Charisma + N6 alinhado (6000 rpm); Grupo 5: Resina Charisma + N6 desalinhado (120 rpm). Foi acrescentada resina na caixa proximal da matriz (Charisma A2, Heraeus Kulzer) e polimerizado por 40 seg. (potência 1100 mW/cm²). A fibra foi embebida em adesivo (Adper Single Bond 2 - 3M ESPE) por 5 min. e fotopolimerizada. Em seguida foi colocado um primeiro incremento de resina e sobre ela depositada a fibra já polimerizada, em seguida o conjunto foi fotoativado em três pontos (extremidades e meio) por 40 s. cada. Em seguida a caixa com resina foi completada. Foi colocada uma tira de poliéster para diminuir a rugosidade superficial. A fotoativação foi realizada igualmente ao passo anterior. Para obtenção dos resultados foi realizado o teste de resistência à fratura com velocidade de 1 mm/min, e célula de carga de 50 Kgf. em máquina de ensaio universal (EMIC mod.DL2000). O teste de Dunnet mostrou que somente os grupos com nanotubo diferiram estatisticamente do grupo controle. O teste ANOVA 2-fatores indica que o fator nanotubo foi significante (p < 0,05) e não existe interação entre os fatores orientação e nanotubo. A presença de nanotubo levou a menores valores de...
Keywords: Resinas compostas; Materiais dentários; Nanotubos de carbono